INNOVATIVE TECHNOLOGIES IN THE ORGANIZATION OF STUDENTS ’SELF-EDUCATION IN THE STUDY OF ECONOMIC DISCIPLINES - Kulishov В. В. (Pedagogy of Higher and Secondary Education, 2022)
The qustions of contemporary forms of samoosvitnoyi of students of economic institutions on the example of distance learning. Shown that the introduction of this form is one of the additional tools that system of educational process and training top professionals.